A transparent water-based metamaterial broadband absorber with a tunable absorption band. (1st January 2023) - Yao, Boyi; Zeng, Qu; Duan, Junping; Wei, Li; Kang, Jinfeng; Zhang, Binzhen
Abstract: In this study, a tunable and optically transparent water-based wideband metamaterial absorber (MMA) is proposed and verified. By adjusting the thickness of the water layer, the conversion of the absorber absorption band from 7.4–22.4 GHz to 23.1–35.5 GHz can be achieved, which demonstrates the flexibility of MMA. Indium tin oxide (ITO) as the resonant and reflective layers of the material structure. Optically transparent polymethyl methacrylate (PMMA) is used as a medium container to encapsulate the water. Furthermore, the suggested MMA is polarization insensitive and has broad incident angle stability. Experiments verify the excellent properties of the proposed MMA. As a result, the suggested MMA has various applications in military and medical equipment optical windows.